6x-3(x-4)=2(x+7)+x

Simple and best practice solution for 6x-3(x-4)=2(x+7)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-3(x-4)=2(x+7)+x equation:


Simplifying
6x + -3(x + -4) = 2(x + 7) + x

Reorder the terms:
6x + -3(-4 + x) = 2(x + 7) + x
6x + (-4 * -3 + x * -3) = 2(x + 7) + x
6x + (12 + -3x) = 2(x + 7) + x

Reorder the terms:
12 + 6x + -3x = 2(x + 7) + x

Combine like terms: 6x + -3x = 3x
12 + 3x = 2(x + 7) + x

Reorder the terms:
12 + 3x = 2(7 + x) + x
12 + 3x = (7 * 2 + x * 2) + x
12 + 3x = (14 + 2x) + x

Combine like terms: 2x + x = 3x
12 + 3x = 14 + 3x

Add '-3x' to each side of the equation.
12 + 3x + -3x = 14 + 3x + -3x

Combine like terms: 3x + -3x = 0
12 + 0 = 14 + 3x + -3x
12 = 14 + 3x + -3x

Combine like terms: 3x + -3x = 0
12 = 14 + 0
12 = 14

Solving
12 = 14

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| p^2-13p+36=0 | | 4x+16=-12 | | 10-2x=9-5x | | 4(3x-5)=4x+4 | | -3p^3+3p^2+6p=0 | | -2x-14=4(x-2) | | 5(x+2)=-40 | | 3m+3=m-1 | | 3(3x+5)-2x=7x+15 | | 3(x-2)2(x+5)=3(x+1)2(x-1)+3 | | (x+3)(x-3)=(x+6) | | 3a+7a=6 | | 2x+10+3x=-12--20 | | 8/7+x+5/7+x | | t^2=4t+3 | | -2x^2+6x-2=-3 | | -4x+1=x+36 | | 16x^2+16x+4=81 | | (x/2)=2 | | 6x^2+20x=-5 | | 8r-13=-31+2r | | 5(1+-1.5)= | | xsquare+49x-456=0 | | 6(3x-6)=3(6x+4) | | 2x+3(4)=2 | | 2x+3(3.25)=2 | | 2x+3(4.5)=2 | | 2x+3(2.5)=2 | | 2x+3(6.8)=2 | | x(3x+2)-5=0 | | -4-7x+5x=-2 | | 14x^2-196x+686=0 |

Equations solver categories